The Effects of Coaching of Head Nurses on the Quality of Discharge Planning Documentations - Candra Dewi Rahayu; Tri Hartiti; Muhamad Rofi'i (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Quality discharge planning will improve the quality of nursing care and the patients’ independence, life quality, and self-efficacy. It also reduces the rate of disease recurrence, the length of stay (LOS), and the cost of care. Coaching is a method to increase professionalism in the delivery of nursing care. Coaching which is performed by nursing managers will enhance the skills, knowledge, and motivation of nurses in providing discharge planning. The aim of this study was to determine the effects of coaching of head nurses on the quality of discharge planning documentations. The study represented a quasi-experimental research with pre-post-test control group design. The samples were 70 nurses and 64 discharge planning documentations selected by non-probability sampling. The statistical analysis used was repeated ANOVA. The test results showed that after the training of coaching of the head nurses, the quality of discharge planning in the control group was 81.647 with a p-value of 0.198, and 98.412 in the intervention group with a p-value of 0.00 (α = 0.05). The results showed that the coaching of the head nurses had a significant effect on improving the nurses’ competence in the documentation of discharge planning. Coaching is a competence that nursing managers should have; therefore, it is suggested that head nurses provide guidance and supervision through continuous coaching to maintain and improve the quality of discharge planning.